Incidence Rate and Risk Factors for Anal Squamous Cell Carcinoma in a Cohort of People Living With HIV from 2004 to 2017: Implementation of a Screening Program. Issue 1 (January 2022) - Milanés Guisado, Yusnelkis; Sotomayor, César; Fontillón, María; Domínguez Castaño, Ana; Espinosa, Nuria; Roca, Cristina; López-Cortés, Luis F.; Viciana, Pompeyo; Neukam, Karin
Abstract : BACKGROUND: Anal squamous cell carcinoma is rare, in general, but considerably higher in HIV-infected men who have sex with men. There is no consensus on the screening of at-risk populations. OBJECTIVE: This study aimed to determine the incidence rates of anal squamous cell carcinoma and the efficacy of a screening program. DESIGN: This is a cohort study (SeVIHanal/NCT03713229). SETTING: This study was conducted at an HIV outpatient clinic in Seville, Spain. PATIENTS: From 2004 to 2017, all patients with at least 1 follow-up visit were analyzed (follow-up group), including a subgroup of men who have sex with men who participated in a specialized program for screening and treating anal neoplasia (SCAN group) from 2011 onward. MAIN OUTCOME MEASURES: The primary outcome measure was the incidence rate of anal squamous cell carcinoma. RESULTS: Of the 3878 people living with HIV included in the follow-up group, 897 were transferred to the SCAN group; 1584 (41%) were men who have sex with men. Total follow-up was 29, 228 person-years with an overall incidence rate for anal squamous cell carcinoma of 68.4/100, 000 person-years (95% CI, 46.7–97.4). The changes in the incidence rate/100, 000 person-years (95% CI) over time was 20.7 (3.40–80.5) for 2004 to 2006, 37.3 (13.4–87.3) for 2007 to 2010, and 97.8 (63.8–144.9) for 2011 to 2017 ( p < 0.001). The strongest impact on the incidence of anal squamous cell carcinoma was made by the lack of immune restoration (adjusted incidence rate ratio (95% CI): 6.59 (4.24–10); p < 0.001), the Centers for Disease Control and Prevention category C (adjusted incidence rate ratio (95% CI): 7.49 (5.69–9.85); p < 0.001), and non-men who have sex with men (adjusted incidence rate ratio (95% CI): 0.07 (0.05–0.10); p < 0.001) in a Poisson analysis. From 2010 to 2017, incidence rates (95% CI) of anal squamous cell carcinoma within the SCAN group and the men who have sex with men of the follow-up group were 95.7 (39.6–202) and 201 (101–386)/100, 000 person-years (adjusted incidence rate ratio (95% CI): 0.30 (0.23–0.39); p <0.001). The incidence rate ratio (95% CI) including non-men who have sex with men in the follow-up group was 0.87 (0.69–1.11); p = 0.269. LIMITATIONS: Adherence to the visits could not be quantified. CONCLUSION: Incidence rates of anal squamous cell carcinoma in people living with HIV increased significantly from 2004 to 2017, especially in men who have sex with men who were not being screened. Participation in the SCAN program significantly reduced the incidence of anal squamous cell carcinoma in men who have sex with men, in whom focus should be placed, especially on those presenting with Centers for Disease Control and Prevention category C and advanced immune suppression. See Video Abstract at http://links.lww.com/DCR/B734 . TASA DE INCIDENCIA Y FACTORES DE RIESGO DEL CARCINOMA ANAL A CÉLULAS ESCAMOSAS EN UNA COHORTE DE PERSONAS QUE VIVEN CON EL VIH DE 2004 A 2017: IMPLEMENTACIÓN DE UN PROGRAMA DE DETECCIÓN: ANTECEDENTES: El carcinoma anal a células escamosas es generalmente raro, pero considerablemente más alto en hombres infectados por el VIH que tienen relaciones sexuales con hombres. No hay consenso sobre el cribado de poblaciones en riesgo. OBJETIVO: Este estudio tuvo como objetivo determinar las tasas de incidencia del carcinoma anal a células escamosas y la eficacia de un programa de detección. DISEÑO: Estudio de cohorte (SeVIHanal / NCT03713229). AJUSTE: Clínica ambulatoria de VIH en Sevilla, España. PACIENTES: De 2004 a 2017, se analizaron todos los pacientes con al menos una visita de seguimiento (grupo F / U), incluido un subgrupo de hombres que tenían relaciones sexuales con hombres que participaron en un programa especializado de cribado y tratamiento de neoplasias anales (SCAN-group) a partir de 2011. PRINCIPALES MEDIDAS DE RESULTADO: Tasas de incidencia del carcinoma anal a células escamosas. RESULTADOS: De las 3878 personas que viven con el VIH incluidas en el grupo F / U, 897 fueron transferidas al grupo SCAN, 1584 (41%) eran hombres que tenían relaciones sexuales con hombres. El seguimiento total fue de 29228 personas-año con una tasa de incidencia general de carcinoma anal a células escamosas de 68, 4 / 100000 personas-año [intervalo de confianza del 95%: 46, 7-97, 4]. El cambio en las tasas de incidencia / 100000 personas-año (intervalo de confianza del 95%) a lo largo del tiempo fue 20, 7 (3, 40-80, 5) para 2004-2006, 37, 3 (13, 4-87, 3) para 2007-2010 y 97, 8 (63, 8-144, 9) para 2011-2017, p <0, 001. El impacto más fuerte en la incidencia del carcinoma a células escamosas anal fue la falta de restauración inmunológica [índice de tasa de incidencia ajustado (intervalo de confianza del 95%): 6, 59 (4, 24-10); p <0, 001], categoría C de los Centros de Control de Enfermedades [índice de tasa de incidencia ajustado (intervalo de confianza del 95%): 7, 49 (5, 69-9, 85); p <0, 001] y no hombres que tenían relaciones sexuales con hombres [razón de tasa de incidencia ajustada (intervalo de confianza del 95%): 0, 07 (0, 05-0, 10); p <0, 001] en el análisis de Poisson. Desde 2010-2017, las tasas de incidencia (intervalo de confianza del 95%) de carcinoma anal a células escamosas dentro del grupo SCAN y los hombres que tienen relaciones sexuales con hombres del grupo F / U fueron 95, 7 (39, 6-202) y 201 (101- 386) / 100000 personas-año [razón de tasa de incidencia ajustada (intervalo de confianza del 95%): 0, 30 (0, 23-0, 39); p <0, 001]. La razón de la tasa de incidencia (intervalo de confianza del 95%), incluidos los no hombres que tenían relaciones sexuales con hombres en F / U, fue de 0, 87 [0, 69-1, 11); p = 0, 269]. LIMITACIONES: No se pudo cuantificar la adherencia a las visitas. CONCLUSIÓNES: La tasa de incidencia del carcinoma anal a células escamosas en personas que viven con el VIH aumentó significativamente de 2004 a 2017, especialmente en hombres que tenían relaciones sexuales con hombres que no se someten a pruebas de detección. La participación en el programa SCAN redujo significativamente la incidencia de carcinoma anal a células escamosas en hombres que tenían relaciones sexuales con hombres, en quienes se debe prestar una especial atención, sobre todo en aquellos que se presentan en la categoría C de los Centros de Control de Enfermedades con inmunodeficiencia avanzada. Consulte Video Resumen en http://links.lww.com/DCR/B734 .